Finite element analysis of thermal stress of laminated composite plates using Taguchi method - Savaş Evran (MANAS: Journal of Engineering)
In present study, thermal stress behavior of laminatedcomposite plates subjected to constant temperature load was investigated usingTaguchi method according to von Mises stress. Numerical thermal stress analyseswere conducted based on L8 orthogonal array including four control factors withtwo levels. Fiber orientation angles of laminates for the plates were used tobe control factors. Finite element analysis of the plates was carried out usingANSYS software. Fiber angles with optimum levels and their effects on thermalstress of plates were detected using analysis of signal to noise (S/N) ratio.Level of importance of laminates and percentage effect ratio of each laminateon von Mises stress were determined according to analysis of variance (ANOVA).